Optical beat interference countermeasures in subcarrier multiplexed wavelength division multiple access networks. - Banat, Mohammad Mahmoud. (University of Ottawa (Canada), 1995)
Several countermeasures to optical beat interference (OBI) in subcarrier multiplexed wavelength division multiple access (SCM/WDMA) networks are presented. The solutions studied in this thesis can be classified in two broad categories: one for which the objective is to expand the OBI spectrum by as much as possible, and one which can theoretically provide complete elimination of OBI. Using the first category of solutions, expanding the OBI spectrum results in less OBI power at the input of the electronic detection circuitry. Using the second category, OBI is reduced substantially by averaging out (using multimode fiber), or by addition and subtraction operations (balanced detection). Increasing the laser intensity modulation index, polarization scrambling, and optical carrier frequency hopping constitute the main solutions in the first category. Balanced detection, and passing the optical fields through pieces of multimode fiber or through a depolarizer are two proposed solutions that theoretically offer OBI elimination. For most of the solutions above, analytical expressions for well-known system performance measures are presented. Performance measures studied include average bit error rate, average carrier-to-interference ratio, and outage probability. Computer simulations and numerical analyses are used whenever appropriate to support or replace the analytical results. The multimode fiber method is verified experimentally, as well. In deriving the signal-to-OBI ratio for the large modulation index solution, a large signal model is used for the first time to describe the laser behavior under direct intensity modulation. Such a model is needed because small-signal models do not provide accurate representation of the modulated laser spectrum at the modulation indices of interest here. While each method discussed in this thesis offers a certain degree of OBI reduction, it is observed that optical frequency hopping (OFH) provides the most significant reduction. OFH is expected to be a very practical scheme in the near future; because the availability of tunable lasers is increasing, and their price is dropping. Even further reduction in OBI power spectral density is expected to be achievable by optical spread spectrum, where the use of coherent ultrashort laser pulses can virtually eliminate OBI, and result in an extremely high network throughput. Such schemes are anticipated to become feasible countermeasures of OBI when all-optical processing becomes well-established.
Keywords: Engineering, Electronics and Electrical.